If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.25x + -18 = 0.5x + -6 Reorder the terms: -18 + 0.25x = 0.5x + -6 Reorder the terms: -18 + 0.25x = -6 + 0.5x Solving -18 + 0.25x = -6 + 0.5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5x' to each side of the equation. -18 + 0.25x + -0.5x = -6 + 0.5x + -0.5x Combine like terms: 0.25x + -0.5x = -0.25x -18 + -0.25x = -6 + 0.5x + -0.5x Combine like terms: 0.5x + -0.5x = 0.0 -18 + -0.25x = -6 + 0.0 -18 + -0.25x = -6 Add '18' to each side of the equation. -18 + 18 + -0.25x = -6 + 18 Combine like terms: -18 + 18 = 0 0 + -0.25x = -6 + 18 -0.25x = -6 + 18 Combine like terms: -6 + 18 = 12 -0.25x = 12 Divide each side by '-0.25'. x = -48 Simplifying x = -48
| 15x+7y=30fory | | 7x+3=-29+3x | | 1.2+x-3.9=-2+5.3 | | Y-14=1(x-2) | | 26m^2-16/49 | | 81-.75x=1.5x | | 1/9x+3=-6 | | 36m^2-49/2 | | 5(a-5)+5=2(a-7) | | 4x-24=6x+36 | | 0.2x+8.7=7.6 | | 7x+y=8fory | | 93=0.36p+.07p | | 93=.036p+.07 | | 543.9-5= | | (y^2-x^2)dx+(xy)dy=0 | | 2xy-5y-x-7=0 | | 4(4x-3)+4=-5 | | (x+2y)dx+(2x+3y)=0 | | 4(x-3)+4=-5 | | a+b=56-14 | | 18-2x=-8x | | 37-19=x-5 | | 14b-9=149 | | 1-4x=1-x | | x-1/2=7/12 | | -14a+b=56 | | 6k-2k=12 | | a-14=56 | | Y-40=-1(x-5) | | 8x^5/3-40=0 | | 8x5/3-40=0 |